POTENTIAL CONTRADICTIONS BETWEEN DEMOCRATIC AND HUMAN RIGHTS PROCESSES IN THE AREA OF MIGRATION AND ASYLUM - Gigauri, George (European Scientific Journal, ESJ, 2013)
Understanding the relationship between alien rights and citizen rights is critical in an era of globalization and migration. State efforts to effectively manage asylum have repeatedly been frustrated by its commitments to international human rights regimes, such as the European Court of Human Rights. Over time, this tribunal has established an effective linkage between the human rights obligations of liberal democracies and their duties towards asylum seekers within their territory. This eventuation has led to the formation of the so called liberal paradox of asylum, reflected in the seemingly contradictory asylum policies of states. In one respect, the government is adopting schemes to deter and penalize migrants, while contrastingly it is embedding human rights, which provide asylum seekers with means to challenge the decision to expel them. This article explores and analyses this apparent contradiction, where increasingly restrictive measures seem to be developing side by side with growing human-rights-oriented inclusive legal practices.